Environmental Monitoring and Thermal Data Analysis Related to Mortality Rates in a Commercial Pig House - Hyo-Jae Seo; Byung-Wook Oh; Il-Hwan Seo (Agriculture)
Diseases in pig houses not only hinder the growth and productivity of pigs but also result in significant economic losses for farmers due to high mortality rates. Although viral infections, including PRRS and PCV-2, are the primary causes, the likelihood of disease onset is closely linked to the pigs’ immune status, which is often compromised by environmental stressors. This study aimed to investigate the relationship between environmental conditions and pig mortality through detailed field monitoring in a commercial pig house with 600 growing pigs. The facility, which experienced a surge in mortality after a ventilation system change, was analyzed for various environmental parameters, including ammonia concentration (range: 7.0–10.7 ppm), dust levels (PM10: 106 µg/m3, PM2.5: 45 µg/m3), ventilation rates (0.49 AER, 67% of design capacity), air temperature (mean: 22.3 °C, range: 18.1–28.7 °C), and relative humidity (mean: 67.4%, range: 55.3–83.2%). Pig mortality and its spatial distribution were recorded, while viral infections were identified using RT-PCR, detecting pathogens such as PRRS, PCV-2, Mycoplasma hyopneumoniae, and Salmonella. Our findings revealed that although dust and ammonia concentrations remained within permissible limits, mortality was significantly correlated with thermal instability. Chronic respiratory diseases were observed in regions where ventilation was concentrated, resulting in daily temperature variations as high as 6.64 °C. The combination of improper ventilation and frequent temperature fluctuations weakened the pigs’ immunity, facilitating the onset of disease. This research underscores the critical role of maintaining stable microclimatic conditions in reducing mortality and highlights the need for advanced automated environmental control systems in smart livestock barns. The insights gained from this study provide a foundational framework for developing precision ventilation and thermal management strategies to enhance productivity and animal welfare.